Sustainable Human Resource Management Practices in Achieving Employees’ Sustainable Performance: Evidence in the Hospitality Sector - Chin, Ying Sin; Abang Azlan, Mohamad; Lo, May Chiun (Huelva University Press, 2023)
Numerous challenges hinder the efforts of many hospitality businesses to improve and maintain the sustainable performance and commitment of employees, primarily due to escalating job demands and expectations. In this investigation, social exchange theory is applied to examine how sustainable HRM practices, including training and development, employee participation, and employment security practices, impact the sustainable performance of executive-level employees in 4- and 5-star hotels. Despite the limited research on the correlation between sustainable HRM practices and employee sustainable performance, particularly within the high-end hotel industry, this study utilized the PLSSEM approach to analyse 280 valid responses. The results indicate a significant correlation between training and development and task sustainable performance. Besides, the study identifies a relationship between employee participation and task and relational sustainable performance, while employment security practice appears to have no effect on either task or relational sustainable performance. Although the research primarily targets executives from 4- and 5-star hotels in Malaysia, which may not be representative of other organisational settings, it provides empirical evidence that sustainable HRM practices are directly linked to task and relational sustainable performance, which is beneficial for both researchers and practitioners.